THE UNIVERSALISTIC AND PARTICULARISTIC COMMUNICATIVE APPROACHES TO THE SOCIAL INTEGRALITY PROBLEM - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with universalistic approach represented by J. Habermas and particularistic approach initiated by M. Foucault to the problem of social integrality through a prism of communication.